Samuel Beckett : the art of rhetoric - Morot-Sir, Edouard; Harper, Howard; McMillan, Dougald (University of North Carolina Press, 2018)
Collected essays from a symposium held in April 1974, at the University of North Carolina at Chapel Hill, this volume analyzes Beckett's philosophy, rhetoric, poetry, and novels.
Originally published in 1976.
Keywords: Beckett, Samuel, -- 1906-1989 -- Criticism and interpretation.; Beckett, Samuel, -- 1906-1989 -- Critique et interprétation -- Congrès.; Beckett, Samuel, -- 1906-1989; Beckett, Samuel.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Rhetorik; Französisch.; Englisch.; proceedings (reports); Conference papers and proceedings; Criticism, interpretation, etc.; Conference papers and proceedings.; Actes de congrès.